Entre o farfalhar das palmeiras e o ramalhar dos carvalhos": o olhar da imprensa catarinense sobre a questão germânica durante a primeira Guerra Mundial (1914-1918) - Bilibio, Rogerio Augusto (2020)
This study proposes, based on the publications from Santa Catarina in the period of the World War I (1914 - 1918), to observe the texts, articles, other materials, which deal with the relationship between the war and the Germans, both in Santa Catarina and in the events that occurred in the battle scene, and its repercussion for the Santa Catarina press. Using newspapers as the main source, the sampling is anchored in four journals, two of them weekly (O Clarão and A Época) and two of daily circulation (O Estado and O Dia), to understand the ideological conduct of each journal, so as to be able to understand as a whole how the Germans and their descendants were the focus of the print media. The select criterion for these journals obeys, almost entirely, that of continuity, since it is the newspapers that circulated in the years when the war occurred, except for the newspaper O Estado, which started its activities in 1915. The study is structured in four moments, where the sources used, the methodologies, the categories created for the analysis of the journalistic content are described, as well as a chapter for each category, namely: the facts of the war and the way they were reported; the Germans in Santa Catarina and the treatment given to them by the newspapers; and finally, a chapter to analyze responsibility for the conflict belongs to the Germans or the allies. The description of journalistic articles, their classification and critical appraisal are conducted based on the categories based on Laurence Bardin's proposition, in a methodology aligned with content analysis. The discussion of the Germanic image in Santa Catarina has repercussions for national movements in relation to the conflict, where three positions stand out: the current aligned with the Germans, called the Germanophile; the current closest to the allies, called the aliadófila; and the current of neutrality. As the main objective of the thesis, it is intended to observe how the image of the Germans was built in Santa Catarina.